Effective in vivo depletion of T cell subpopulations and loss of memory cells in cattle using mouse monoclonal antibodies - Naessens, Jan; Scheerlinck, J.P.; Buysscher, E.V. de; Kennedy, D.; Sileghem, M.R. (Elsevier, 1998)
Conditions were established to obtain depletion of T lymphocyte subsets in lymphoid tissues of calves by injection of mouse monoclonal antibodies to T cell antigens. Adverse reactions were avoided by injecting small quantities of antibody until target cells had disappeared from blood. Two different mechanisms appeared to be responsible for elimination of the target cells. Rapid depletion of T cells was associated with complement-binding antibody isotypes (IgG2a, IgM), suggesting a complement-mediated mechanism. Clearance of T cells after several days was observed with a noncomplement-binding isotype (IgG1). Suggesting phagocytosis or induction of apoptosis as possible mechanisms. Clearance of the cells in peripheral blood and spleen was obtained with 10-20 mg of anti-CD4 or anti-CD8 but almost ten times as much was needed to obtain depletion of the cells in lymph nodes and Peyer's patches. Depletion lasted for 12 days for CD4 T cells and 3 weeks for CD8 T cells. Successful and lasting depletion (at least 2 weeks) was also obtained with other T cell reagents such as anti-CD2 and anti-WC1 (gamma/omega) T cells. Although B lymphocytes could be removed by a complement-binding antibody, complete depletion of these cells only lasted for a few hours probably because B cells regenerate faster than T cells. T cell function was severely inhibited when CD4- T cells were depleted. Stimulation of T cells with foot and mouth disease viral antigen (FMDV) in vaccinated calves was non-existent after depletion. Even 2 months after restoration of normal CD4- T cell levels in blood activity to FMDV was low. This suggested that the depleted T cells were repiaced by naive cells.